2019
DOI: 10.56093/ijas.v89i2.87017
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epistasis, additive and dominance components of variation for seed yield and its attributes in Indian mustard (Brassica juncea)

Abstract: This study was conducted to detect epistasis and importance of additive and dominance variances for seed yield and contributing traits using 27 progenies produced by crossing nine lines with three testers, viz. NPJ 112, RRN 727 and their F1 in triple test cross fashion. Analysis of variance revealed the existence of epistasis for all the traits except secondary branches/plant and oil content. Its partitioning showed higher magnitude of (i) type for days to flowering, days to maturity and primary branches and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
4
13
0
Order By: Relevance
“…These parents can be included in breeding progamme for yield improvement. Similar findings had also been reported by Singh et al (2005), Singh et al (2013) and Meena et al (2015) in Indian mustard with different set of materials. A total of six crosses, viz.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These parents can be included in breeding progamme for yield improvement. Similar findings had also been reported by Singh et al (2005), Singh et al (2013) and Meena et al (2015) in Indian mustard with different set of materials. A total of six crosses, viz.…”
Section: Resultssupporting
confidence: 89%
“…The heterosis breeding needs testing of the genetic value of parental lines for production of superior recombinants. The line × tester mating design (Kempthorne 1957) has been extensively used in Indian mustard to analyze the combining ability effects and to provide information regarding genetic mechanisms controlling seed yield and yield attributing traits (Parmar et al 2011, Yadava et al 2012, Singh et al 2013, Meena et al 2015. Knowledge of gene action and estimation of general and specific combining ability effects (GCA and SCA) are important parameters, as they provide an essential tool to the breeders in selection of better parental combinations for further improvement in rapeseed-mustard crops.…”
mentioning
confidence: 99%
“…The number of secondary branches/plant, weight of 100 seeds, and yield/plant showed positive and substantial GCA impacts. Kang et al (2013), Meena et al (2015), and Mahmud et al (2009) also found positive and significant GCA effects for plant height, numbers of seeds/silique, primary branches/plant, secondary branches/plant, and yield-related traits in Brassica rapa. Shah et al (2021) reported similar results for yield/plant, oil%, daysmaturity, plant height, numbers of branches/plant, siliques on the main branch, total silique/plant, and seeds/silique.…”
Section: General Combining Ability Effectsmentioning
confidence: 95%
“…(Ehrenreich and I.M 2017) Epistasis has been classi ed into additive × additive (i), additive × dominance (j) and dominance × dominance (l) types based on the nature of gene action involved. Several studies have reported the presence of epistatic effects for yield and yield-related traits in Brassica species (Meena et al 2019). These studies revealed that epistasis among loci (with or without detectable main effect) play a signi cant role in controlling heterosis in Brassica species.…”
Section: Introductionmentioning
confidence: 99%